PENERAPAN TEKNOLOGI POWDER METALURGY UNTUK PEMBUATAN KOMPONEN MESIN BERBASIS PASIR BESI LOKAL - Murjito . (Jurnal Gamma, 2010)
Metalurgi powder is a commercial workpiece forming process of metal where the metal wasdestroyed first in the form of flour, then flour is pressed in the mold (mold) and heated below themelting temperature of the workpiece to form dust. So that the metal particles fuse because themechanism of mass transport due to diffusion of atoms between the particle surface. Powdermetallurgy method provides a rigorous control on the composition and use of mixtures that can notbe fabricated by other processesIn this study the process of soft magnetic iron production by mechanical alloying powderprocess-based yan metalurgy local iron sand. Base backdrop that the use of local sand from the datawe can from the foundry industry raw materials and large penunjangsebagian still imported. Materialsthat are 100% pengadaanya still relies imported materials are iron ore and alloys (Alloy).Iron filings and sand powder 100 mesh size locally has mixed for 20 minutes. The amount ofpowder added is 25%, 50%, and 75% by weight. Powder which had sifted and mixed and theninserted into molds (dies) that has been coated by the lubricant of zinc stearate on the walls of themold then dikompaksi both single-action pressing with a pressure of 2000 psi in order to obtain asample form of tablets. Sintering temperature of 1000 0C for 30, 60, and 90 minutes later performeddapur.Pengamatan cooling micro structure used optical microscopy and Vickers hardness testsperformed.The results of this study is the optimal value of remanent induction at 25% by weight of sandsintered 90 minutes by 9.4 Gauss and an optimal value of Vickers hardness at 75% by weight ofsand sintered 90 minutes at 501 HV.